SEISMIC FACIES ANALYSIS ON 2D SEISMIC REFLECTION PROFILE IN BARUNA AND JAYA LINE AT NORTH EAST JAVA BASIN - Wiguna, Taufan; Rahadian, Rahadian; Ardhyastuti, Sri; Rahmah, Safira; Zera, Tati (Jurnal Neutrino, 2016)
Two dimension (2D) seismic profile of Baruna and Jaya lines at North-East Java Basin show seismic reflector characteristics that can be used to interpret sediment thickness and continuity. Those reflector characteristics that can be applied for seismic facies analysis that represent depositional environment. This study starts from seismic data processing that using Kirchhoff Post Stack Time Migration method which is 2D seismic profile as result. Seismic reflector characterization has been done to both 2D profiles. Seismic reflector characterization was grouped as (i) individual reflection, (ii) reflectionÂ  configuration, (iii) reflection termination, (iv) external form. Individual reflection characteristics show high and medium amplitude, medium and low frequency, and continuous. Configuration reflection is continuous with parallel and subparallel type. Reflection termination shows onlap, and external form shows sheet drape. Local mound appearance can be interpreted as paleo-reef. Facies seismic anlysis result for this study area is shelf.